Efficacy of Lajjabati (Mimosa pudica) and Daruchini (Cinnamomum verum) extracts on wound healing in rabbits - Rukhsana Amin Runa; Md. Abdur Rahim Prodhan; Suravi Akter; Afrina Mustari (PLoS ONE, 2026)
Plant and herbal preparations are traditionally used in wound management to promote healing. The study aimed to explore the therapeutic efficacy of Lajjabati ( Mimosa pudica ) leaves and Daruchini ( Cinnamomum verum ) paste on wound healing and the histo-architectural changes in the wounded skin of rabbits. Sixteen rabbits, weighing between 1.5 and 2 kg, were divided into four groups: A, B, C, and D, each containing 4 rabbits. Surgical incisions were made on the skin of the rabbits, creating a total of 32 wounds, two for each rabbit. Lajjabati ( Mimosa pudica ) leaves, Daruchini ( Cinnamomum verum ) paste, and a combination were applied to the skin wounds in Groups A, B, and C, respectively. Group D was considered the control. The morphological characteristics of wound healing, such as the swelling of sutured areas, elevation of the suture line, width of the sutured area, and contraction length, were recorded from Day 0 to Day 21. Bacteriological and histopathological samples were collected on Day 3, 7, and 14 for analysis. The swelling of the sutured area and elevation of the sutured line were 11.50 ± 0.13 and 2.54 ± 0.10 mm in Group A, which were significantly lower compared to other groups. The histopathological study revealed the presence of marked inflammation, hyperplasia, and enlargement of glands in Groups B and C, whereas in Group A, all tissues appeared to be normal, and hair follicles started to grow on Day 7. In microbiological study, the lowest bacterial colonies were observed in Group A. It is concluded that Lajjabati ( Mimosa pudica ) paste is more effective in the wound healing process. Daruchini ( Cinnamomum verum ) can also be used, but it causes more tissue reactions, indicating delayed healing of cutaneous wounds.